2015
DOI: 10.1016/j.chiabu.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Children's experiences of corporal punishment: A qualitative study in an urban township of South Africa

Abstract: Exposure to violence is a serious mental and public health issue. In particular, children exposed to violence are at risk for poor developmental outcomes and physical and mental health problems. One area that has been shown to increase the risk for poor outcomes is the use of corporal punishment as a discipline method. While researchers are starting to ask children directly abouttheir experiences of violence, there is limited research with children about their perspectives on physical punishment, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 42 publications
(59 reference statements)
3
37
1
4
Order By: Relevance
“…In consistency with our findings, Feinstein and Mwahombela (2010) found similar feelings as negative consequences of corporal punishment in Tanzania. Similarly, in a study by Breen, Daniels, and Tomlinson (2015), it was reported that the most common emotional response was a feeling of sadness for being beaten at home, whereas anxiety and feelings of worry about being punished were prevalent at school.…”
Section: Discussionmentioning
confidence: 86%
“…In consistency with our findings, Feinstein and Mwahombela (2010) found similar feelings as negative consequences of corporal punishment in Tanzania. Similarly, in a study by Breen, Daniels, and Tomlinson (2015), it was reported that the most common emotional response was a feeling of sadness for being beaten at home, whereas anxiety and feelings of worry about being punished were prevalent at school.…”
Section: Discussionmentioning
confidence: 86%
“…Children in India, Republic of Korea, South Africa, Sudan, Swaziland, the United States, and Zambia have reported being subject to corporal punishment for a range of behaviors, including not doing their homework, coming late to class, bringing cell phones to school, running in the hallway, sleeping in class, answering questions incorrectly, having an unacceptable appearance, using bad language, writing in a text book, failing to pay school fees, making noise in class, and being absent (Beazley et al, 2006; Breen, Daniels, & Tomlinson, 2015; Clacherty, Donald, & Clacherty, 2005a; Clacherty et al, 2005b; Elbla, 2012; Human Rights Watch & ACLU, 2008; Mitchell, 2010; Morrow & Singh, 2014). Students also report that an entire class may be subject to corporal punishment for the misbehavior of a single student or because an entire class or school performs poorly on examinations (Beazley et al, 2006; Pinheiro, 2006).…”
Section: Definition and Forms Of School Corporal Punishmentmentioning
confidence: 99%
“…Kekerasan yang banyak terjadi terhadap anak baik berupa kekerasan secara fisik maupun kekerasan secara nonfisik.Namun karena kesadaran masyarakat yang kurang, maka terkadang kekerasan yang terjadi terhadap anak itu dianggap sebagai hal yang wajar. Hal ini disebabkan karena hal tersebut terjadi secara berulang-ulang, sehingga hal tersebut dianggap menjadi suatu kewajaran dan bisa saja dianggap benar (Hartanto, 2009;Breen et al, 2015).…”
Section: Evi Widowati Dan Widya Hary Cahyatiunclassified